(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study’s goal was to look into the approaches employed to instruct students who had reading and writing difficulties in a typical classroom. How students are with reading and writing difficulties taught in a typical classroom was the study’s major question. Cognitive processes of brain are affected by numerous factors such as genetic and neurobiological which may alter the functioning of brain causing difficulties in learning. The basic learning skills like reading and writing are of great significance in the foundational years. Individuals who are having these difficulties are not as quick as their peers’ and might find certain aspects of learning challenging. Problem in reading occurs when a pupil experiences difficulty in reading single word, comprehension, sounding out letters/words. While, difficulty in writing arises when a learner is not able to communicate his ideas in writing, mistakes in spelling and incorrect framing of sentences. Moreover, sometimes, due to mirror writing or writing letters upside down, it gets really difficult to read their handwriting.